Evaluation of antioxidant-related properties of six colored varieties of carrots (Daucus carota L.) - Le, Thi Van Anh; Mai, Thi Phuong Nga (Vietnam Journal of Biotechnology, 2025)
Carrots (Daucus carota L.) are a prevalent vegetable in human diet nutrition and are an excellent source of vitamins, alpha- and beta-carotene, and antioxidant compounds. Carrots are categorized primarily according to the pigmentation of their tuberous roots, which can range from white, yellow, orange, purple, and black. This study aims to determine the antioxidant-related properties of six carrot varieties collected in Vietnam, including the total phenolic content (TPC), the total flavonoid content (TFC), DPPH scavenging activity, and the antioxidant enzyme activities. The results showed that the black carrot extract had the lowest IC50 value whereas the highest belonged to the orange carrot. Furthermore, the findings revealed that black carrots exhibited the highest TPC, which was 1.24 ± 0.01 (g GAE/100 g sample) whereas the red-orange carrots had the lowest TPC, which was 0.3 ± 0.05 (g GAE/100 g sample). Additionally, the black carrots also had the highest TFC, which was 161.32 ± 1.68, and the red-orange carrots had the lowest TFC value which was 27.6 ± 0.80 (g QE/100 g DW). The antioxidant enzyme activities resulted in the highest peroxidase activity of black carrots (149.48 ± 2.25 U/mg protein) and the highest catalase activity of purple carrots (93.19 ± 3.28 U/mg protein). Phytochemical analysis indicates that black and purple carrots exhibit higher antioxidant potential, suggesting their applicability in treatments and as agents for food preservation.